Concurrent Testicular and Bladder Cancer in a 57-year-old Man - Esther Han; Daniel M. Stein; Dongping Shi; Ranko Miocinovic (Urology Case Reports, 2015)
We present a rare finding of concurrent right testis non-seminomatous mixed germ cell tumor and muscle invasive urothelial carcinoma of the bladder in a 57-year-old homeless man. The socioeconomic factors and the disease presentation caused a treatment dilemma in terms of the appropriate type of neoadjuvant chemotherapy. The patient ultimately underwent upfront surgery with retroperitoneal lymph node dissection and radical cystoprostatectomy followed by adjuvant cisplatin-based chemotherapy.